Terminal decline in well-being: The role of social orientation - Denis Gerstorf; Christiane A. Hoppmann; Corinna E. Löckenhoff; Frank J. Infurna; Jürgen Schupp; Gert G. Wagner; Nilam Ram (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Well-being development at the end of life is often characterized by steep deteriorations, but individual differences in these terminal declines are substantial and not yet well understood. This study moved beyond the typical consideration of health predictors and explored the role of social orientation and engagement. To do so, we made use of social variables at the behavioral level (self-ratings of social participation) and the motivational level (valuing social and family goals), assessed two to four years before death. We applied single- and multi-phase growth models to up to 27-year annual longitudinal data from 2,910 now deceased participants of the nation-wide German Socio-Economic Panel Study (SOEP; ageat death: M = 74 years; SD = 14; 48% women). Results revealed that leading a socially active life and prioritizing social goals in late life were independently associated with higher late-life well-being, less pronounced late-life decline, and a lateronset of terminal decline. Significant interaction effects suggested that the effects of (reduced) social participation and (lowered) social goals were compounding each other.compound. Findings also indicated that less decline in social participation was associated with shallower rates and a later onset of well-being decline. We found little evidence that valuing family goals is associated with late-life trajectories of well-being. Associations were independent of key correlates of well-being and mortality, including age at death, gender, education, disability, hospital stays, and goals in other life domains. We discuss possible pathways by which maintaining social orientation into late life may help mitigate terminal decline in well-being.
Keywords: 330; successful aging; life satisfaction; social support; longitudinal change; development; mortality; German Socio-Economic Panel Study; SOEP